„Człowiek z miasta” w świetle tekstów regionalnych z przełomu XIX i XX wieku - Kurzydło, Rafał (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2010)
The article presents the perception the city and its inhabitants in the imagination andbehaviour of the inhabitants of Iwkowa, a village in the Malopolska region, in the poviat ofBrzesko. The material underlying the research includes 122 short stories published in twovolumes under the titles Gawędy iwkowskie (Tales from Iwkowa) and Komedyje iwkowskie(Comedies from Iwkowa). The examined short stories display a clear-cut division of the worldinto orbis interior and orbis exterior, and thus also present the dichotomy ”familiar - foreign”.The article shows not only the cultural conditioning, but also the dominating linguisticbehaviour, which is characterized by schematization, stereotype, and simplified evaluation ofthe contact with ”the strangers” - the city people (e.g. by means of generic subjects, specificderivational processes to denote the strangers, elements of grotesque, or animalistic similes).Although at the turn of the 20th century certain ”warming” of the city - countryside relationscould be perceived, in the context of the analysed texts the dominating attitude to the city andthe city people is the negative stereotype.